COOPERATIVE LEARNING THINK PAIR SHARE IMPROVING STUDENT COOPERATION - Siti Fatimah; Muhammad Agus Kurniawan (Jurnal Ilmiah AZZIQRI: Kajian Keislaman dan Kependidikan, 2023)
Human nature as a social being is a real thing where all humans are dependent on one another. This shows that cooperation is something that is really needed by everyone. The problems faced in the world of education today are student cooperation that is not yet optimal and low student learning outcomes in the teaching and learning process. One alternative problem solving to improve student cooperation is to use Think Pair Share cooperative learning. With this model, students are given the opportunity to work alone, work together with small groups of students and are trained in social communication interactions and are accustomed to sharing knowledge, experiences, assignments and responsibilities. Therefore, through Think Pair Share cooperative learning,